PEMBERDAYAAN MASYARKAT MELALUI PENYULUHAN KESEHATANDEMAM BERDARAH DENGUE PADA MASYARAKAT DI DUSUNKEDUNGJAGO DESA KEDUNGREJO KECAMATANPURWODADI KABUPATEN GROBOGAN - Wahyu Riniasih; Rini Sri Purwati; Bagus Indra Pamungkas; Desyika mayasari; Evi Puspitasari; Farhan Muhammad Najib (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a disease   caused by the dengue virus which is spread through the bite of   the Aedes mosquito, especially the Aedesa egypti, which is the   fastest growing mosquito throughout the world. Transmission   of this virus is more likely to occur in countries with tropical   and subtropical climates. This is associated with increasing   temperatures, and changes in the rainy and dry seasons are   considered factors that increase the risk of dengue virus   transmission (Slani et al., 2024). Metodology : carry out nonphysical intervention programs such as health education about   Dengue Hemorrhagic Fever (DHF). This activity consists of 3   stages, namely planning, preparation and implementation. In the planning stage, students coordinate with the hamlet head, village midwife, RT head, for observations and discussions regarding Dengue Hemorrhagic Fever (DBD) education..Results: The results of implementing activities in health education about dengue hemorrhagic fever (DHF) can be seen after the health education by asking respondents to explain again what has been explained, with the results of respondents experiencing an increase in the sufficient knowledge category, namely 18 respondents (93.3%) and experiencing a decrease in the category Lack of knowledge, namely 2 respondents (6.7%). output achieved. Conclusion: Through the implementation of the activity "Health Education on Preventive Efforts and Methods of Transmission of DHF" in general it can be concluded that the public's understanding of how to prevent and transmit DHF is still not evenly distributed so that service activities like this still need to be carried out on an ongoing basis to ensure the correctness and accuracy of information regarding prevention efforts. and dengue fever transmission.